Blood Supply of Cranial Nerves Passing Through the Cavernous Sinus: An Anatomical Study and Its Implications for Microsurgical and Endoscopic Cavernous Sinus Surgery - Najera, Edinson; Ibrahim, Bilal; Muhsen, Baha’eddin A.; Ali, Assad; Sanchez, Clariza; Obrzut, Michal; Borghei-Razavi, Hamid; Adada, Badih (Frontiers in Oncology, 2021)
Background Despite improvements in surgical techniques, cranial nerve (CN) deficits remain the most frequent cause of disability following cavernous sinus (CS) surgery. The most common tumor affecting the CS is meningioma. They originate from lateral wall and have their blood supply from meningohypophyseal trunk (MHT) and inferolateral trunk (ILT). Pituitary adenomas commonly invade the CS through its medial wall and receive blood supply form medial branches of the internal carotid artery (ICA) (superior and inferior hypophyseal arteries). Some tumors may grow within the CS (e.g. trigeminal schwannomas, hemangiomas). These tumors are fed by all the intracavernous ICA branches. Tumors involving the CS may also displace the neurovascular structures, therefore, a better understanding of intracavernous neurovascular anatomy may reduce the postoperative morbidity associated with approaching CS tumors. In this anatomical study, the anatomic variations and their clinical implications of the intracavernous CNs’ blood supply were evaluated through transcranial and endonasal routes. Methods Twenty sides of ten adult cadaveric formalin-fixed, latex-injected specimens were dissected in stepwise fashion under microscopic and endoscopic magnification. The origin and course of the intracavernous ICA branches supplying the intracavernous CNs are studied. Results The proximal segment of the oculomotor nerve receives blood supply from the ILT in 85%, and the tentorial artery of the MHT in 15% of specimens. The distal segment is exclusively supplied by the ILT. The proximal trochlear nerve receives blood supply from the ILT (75%) and the tentorial artery (25%); the distal segment is exclusively supplied by the superior orbital branch. The proximal third of the abducens nerve receives its vascularity exclusively from the dorsal meningeal artery, and its middle and distal thirds from the ILT. The ophthalmic and proximal maxillary segments of the trigeminal nerve also receive blood supply from the ILT. The distal maxillary segment is supplied by the artery of the foramen rotundum. All ILT branches terminate on the inferomedial aspects of the intra-cavernous CNs. Extensive anastomoses are found between ILT branches and the branches arising from external carotid artery. Conclusion Understanding the anatomy of the intracavernous ICA’s branches is important to improving surgical outcomes with tumors involving the CS.